PERENCANAAN PELEBARAN JEMBATAN DESA TAMANSARI - Robby Bastian; Rulhendri Rulhendri (Lembaga Penelitian dan Pengabdian kepada Masyarakat UIKA Bogor, 2023)
The bridge is a connecting road whose benefits are very visible for the mobility of residents to connect the village with other villages, so that this connecting road is one of the accesses for residents to travel. Along with the increasing number of residents and also the number of vehicles owned by residents, if there is high enough rainfall it causes runoff of rainwater to inundate the bridge, therefore the size of this bridge must be carefully calculated so that it does not become a disaster for the community.